The Cambridge Companion to Nelson Mandela - Conradie, Marthinus (University of the Free State, 2015)
Abstract not available
Barnard, Rita (ed). (2014). The Cambridge Companion to Nelson Mandela. New York: Cambridge University Press. ISBN 978-1107600959.
Keywords: Mandela, Nelson Rolihlahla; Book review